Clinical outcome of pneumococcal meningitis during the emergence of pencillin-resistant Streptococcus pneumoniae: an observational study - Gouveia, Edilane L (BioMed Central, 2011)
BACKGROUND: Prior to the availability of generic third-generation cephalosporins, penicillins were widely used for treatment of pneumococcal meningitis in developing countries despite concerns about rising levels of penicillin resistance among pneumococcal isolates. We examined the impact of penicillin resistance on outcomes of pneumococcal meningitis over a ten year period in an infectious diseases hospital in Brazil. METHODS: Clinical presentation, antimicrobial therapy and outcomes were reviewed for 548 patients with culture-confirmed pneumococcal meningitis from December, 1995, to November, 2005. Pneumococcal isolates from meningitis patients were defined as penicillin-resistant if Minimum Inhibitory Concentrations for penicillin were greater than 0.06 μg/ml. Proportional hazards regression was used to identify risk factors for fatal outcomes. RESULTS: During the ten-year period, ceftriaxone replaced ampicillin as first-line therapy for suspected bacterial meningitis. In hospital case-fatality for pneumococcal meningitis was 37%. Of 548 pneumococcal isolates from meningitis cases, 92 (17%) were resistant to penicillin. After controlling for age and severity of disease at admission, penicillin resistance was associated with higher case-fatality (Hazard Ratio [HR], 1.62; 95% Confidence Interval [CI], 1.08-2.43). Penicillin-resistance remained associated with higher case-fatality when initial therapy included ceftriaxone (HR, 1.68; 95% CI 1.02-2.76). CONCLUSIONS: Findings support the use of third generation cephalosporin antibiotics for treatment of suspected pneumococcal meningitis even at low prevalence of pneumococcal resistance to penicillins.